Разработка условий хроматографического разделения пространственных изомеров 4,5-дигидросиимидазолидин-2-тиона - Иванова К. Е.; Дементьева Н. Б.; Никулина А. Е.; Котельников О. А.; Мальков В. С.; Новиков Д. В. (2017, 2017)
Заглавие с экрана